The strategic use of embolization in treating infantile fibrosarcoma-related heart failure: a case report - Bartoli, M. E.; Cassanelli, G.; Natali, G. L. (Frontiers in Surgery, 2025)
IntroductionInfantile fibrosarcoma (IFS) represents the most common non-rhabdomyosarcoma soft tissue tumor, with 80% of diagnoses under the first year of life. In contrast with adult fibrosarcoma, IFS has lower risks of metastasis, better long-term survival rate, and higher chemosensitivity. Conservative surgery, in association with chemoradiotherapy in case of metastasis or recurrence, usually represents the gold standard treatment.CaseWe examined the case of a 2-month-old female patient affected by retroperitoneal congenital fibrosarcoma, which had caused high-flow heart failure (HFHF) due to its hypervascularization and multiple arteriovenous fistulas. Given the complexity of the case and its atypical vascularization, after multidisciplinary discussion, we decided to perform an endovascular approach rather than a surgical one, aiming to interrupt pathological flow to this abdominal mass. The procedure was well tolerated with fast improvement in both clinical and ultrasound markers of heart failure.ConclusionThis is the first instance of arteriographic application for the management of HFHF caused by hypervascularized retroperitoneal IFS that we are aware of. In conclusion, we advise using this approach because of its safety and effectiveness, even though it necessitates a high level of experience.